(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Internet banking is changing the banking industry and is having the major effects on banking relationships. Internet banking involves use of Internet for delivery of banking products services. It falls into four main categories, from Level 1 - minimum functionality sites that offer only access to deposit account data - to Level 4 sites - highly sophisticated offerings enabling integrated sales of additional products and access to other financial services- such as investment and insurance. The study is an exploratory cum descriptive. Primary data has been used by the researcher to achieve the objectives of the study. Convenience sampling technique has been used to collect the data.